A century later, resolving Joseph Grinnell's "striking case of adventitious coloration". (10th May 2017) - Levitis, Daniel A.; Golan, Jacob; Pringle, Anne; Taylor, John
Abstract: In 1921, The Auk published an unresolved mystery submitted by Joseph Grinnell, founding director of the Museum of Vertebrate Zoology at the University of California, Berkeley. He had collected two Oak Titmice ( Baeolophus inornatus ) whose breast feathers appeared to be yellow; the feathers were covered in microscopic particles. He invited readers to further investigate the nature of these particles. Nearly a century later, we have determined that Grinnell's mysterious grains are willow ( Salix ) pollen, a diagnosis he rejected because the size of the particles had been mismeasured, and because he lacked a plausible explanation for how the birds would become coated in pollen. We investigated this case using Grinnell's own specimens, field notes, and correspondence, a testament to Grinnell's dedication to scientific rigor through carefully documented and curated natural history collections.